Availability and exploitation of lithic raw materials in Las Chapas locality (Chubut province, Argentina) - Schuster, Verónica; Massaferro, Gabriela Isabel; Iglesias, Claudio (Arqueología, 2023)
This paper aims to evaluate the availability and distribution of the primary lithic raw material sources recognized in the archaeological locality of Las Chapas (Mártires department, Chubut province), stressing the lithological variability, spatial distribution, and rock knapping quality. The results show that there is a varied distribution and availability of local primary lithic raw materials (basalt, opal, jasper), even though their quality for lithic reduction goes from regular to low, except for the silicified tuff. The pebbles were evaluated as a secondary lithic raw material source since their lithologies are usually absent in the local archaeological context. Opal and chalcedony are the most abundant lithic material in the studied archaeological sites and they could be of local origin, although no probable lithic source has been found yet. The information presented here is a first approach to the analysis of the potential sources of lithic raw material in Las Chapas, being the major future goal to develop a solid database for the lower-middle area of the Chubut river valley.